Assessment Literasi Sains Dimensi Kompetensi pada Materi Pamanasan Global - Evi Setiawani; Nurul Apsari; Novika Lestari (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2021)
Abstract: The purpose of this study is to describe the scientific literacy ability of the competency dimension in the material of global warming class XI MIPA and XI IIS.  This research uses quantitative methods with descriptive analysis techniques. The research sample was 30 students of class XI MIPA and 30 students of class XI IIS at Bhakti Setia Nanga Pinoh High School in the 2019/2020 school year.  The research instrument used was a scientific literacy test taken from the book Take the Test: Sample Question from the OECD's PISA Assessment.  The results of the analysis show the scientific literacy ability of the competency dimension in class XI MIPA with the highest percentage achievement being the indicator explaining the potential implications of scientific knowledge for the community by 63% and the lowest achievement being the indicator identifying the questions discussed in a scientific study by 37%.  Whereas the scientific literacy ability profile of the competency dimension in class XI IIS with the highest percentage achievement was in the indicators drawing conclusions based on data with a percentage of 43% and the lowest achievement was in the indicator explaining how to explore the questions scientifically given by 23%.  Thus, the need for learning and evaluation processes based on scientific literacy assessment of competency dimensions.Keywords: Scientific literacy, assessment, competence, global warmingAbstrak: Tujuan dari penelitian ini adalah mendeskripsikan kemampuan literasi sains dimensi kompetensi pada materi pemanasan global kelas XI MIPA dan XI IIS. Penelitian ini menggunakan metode Kuantitatif dengan teknik Analisis Deskriptif. Sampel penelitian adalah 30 siswa kelas XI MIPA dan 30 siswa kelas XI IIS di SMA Bhakti Setia Nanga Pinoh pada tahun ajaran 2019/2020. Instrumen penelitian yang digunakan adalah soal tes literasi sains yang diambil dari buku Take the Test: Sample Question from the OECD's PISA Assessment. Hasil analisis memperlihatkan kemampuan literasi sains dimensi kompetensi pada kelas XI MIPA dengan capaian persentase tertinggi berada pada indikator menjelaskan implikasi potensial pengetahuan ilmiah bagi masyarakat sebesar 63% dan capaian terendah berada pada indikator mengidentifikasi pertanyaan yang dibahas dalam sebuah penelitian ilmiah sebesar 37%. Sedangkan profil kemampuan literasi sains dimensi kompetensi pada kelas XI IIS dengan capaian persentase tertinggi berada pada indikator menarik kesimpulan berdasarkan data dengan persentase sebesar 43% dan capaian terendah berada pada indikator menjelaskan cara mengeksplorasi pertanyaan yang diberikan secara ilmiah sebesar 23%. Dengan demikian, perlu adanya proses pembelajaran dan evaluasi berbasis assessment literasi sains dimensi kompetensi.Kata-kata kunci: Literasi sains, assessment, kompetensi, pemanasan global